Ação rescisória fundada em posterior decisão de inconstitucionalidade do Supremo Tribunal Federal - Santana, Gabriel de Oliveira Coelho (2024)
This work seeks to analyse the rescission action based on subsequent unconstitutionality decision by the Federal Supreme Court which is in art. 525, § 15 and art. 535, §8º, Code of Civil Procedure, searching to analyse its interpretative and temporal limits. To achieve this goal, it was searched to identify the contemporanious dimesions of legal certainty, which is not a principle based on an all-or-nothing idea, but that brings a requirement of calculability, reliability and knowability. Given this dimesions of legal certainty, it was identified how they are related with res judicata, especially with regard to preclusive efficacy. After this, it was studied the atipycal relativization of “unconstitutional res judicata” theory, to investigate how the unconstitutionality and the res judicata are related, and also the repercussions that this doctrinal current had on legislation. It was also investigated how do the effects of the unconstitutionality decision operates in in the Brazilian legal system, as well if there is any constitutional obstacle to the establishment of a hypothesis of rescission action based on a subsequent decision of the Federal Supreme Court. After these analyses, the interpretative limits of the rescission action of art. 525, §15 and 535, §8º, Code of Civil Procedure were properly investigated, ocasion in which it was proposed an interpretative possibility that was in line with the principle of legal certainty, limiting its scope of incidence. Finally, it was analysed how the effects modulation influences in this rescission action, as well the possibility that this techinic may be used not only by the Federal Supreme Court, but also by the ordinary court that makes the judgment of the rescission demand based on subsequent unconstitutionality decision